Human Prosperity Measurement within The Gloom of Maqasid Al-Shariah - Malik Shahzad Shabbir (Global Review of Islamic Economics and Business, 2019)
This study is trying to interpret the theory of Maqasid Al-Shariah in wide context, which further based on the measurement of socio-economic prosperity; it takes into account the major drawbacks of the existing measurements. The proposed measurement is an integrated Maqasid Al-Shariah based composite index to measure socio-economic prosperity of economies in general and muslim countries in particular. The integrated Maqasid Al-Shariah based measurement does not isolate economic and social progress from the spiritual and biophysical variables that effect human prosperity. Specifically, in this paper, we will be looking at the theory of Maqasid Al-Shariah and socio-economic prosperity, in order to develop these constructs within the proposed composite index and the measurement variables, where each variable constructs under the Maqasid Al-Shariah. This study argues that the existing measurements of socio-economic progress are limited by number of measured variables and, therefore, do not portray the real socio-economic prosperity status.